Analysis of Some Communication-Related Queuing System Modeling and Performance - Al-Matar, Najeeb (Faculty of Engineering, Wijaya Putra University, 2023)
The paper presents research into the analysis of queuing systems in the context of communication, with the goal of creating precise models and evaluating their efficacy. The importance of queueing systems cannot be overstated in fields as disparate as telecommunications, computer networks, and the service sector. Analyzing how these systems function allows us to better allocate resources, boost performance, and provide a better experience for end users. The main goals are to create mathematical models that precisely capture the queuing behavior and to assess the effectiveness of these models in terms of metrics like queue length, waiting time, and system utilization. To do so, it is necessary to perform an extensive analysis of the relevant literature and theoretical frameworks. The properties of communication-related systems are examined, and many queuing models, including the M/M/1, M/M/c, and M/G/1, are modified accordingly. In addition, simulation methods are used to verify the accuracy of the suggested models and assess how they would fare in practical applications. The research yields useful information on the dynamics of queuing systems used in the field of communication. They show how changes to the arrival rate, service rate, and number of servers affect the system's most important performance indicators. Different scheduling policies, routing tactics, and resource allocation methodologies are also investigated to determine their impact on system performance.